Synergies for sustainable energy - Yüzügüllü, Elvin (Artech House, 2013)
Here's a one-stop volume that takes a unique approach to addressing today's complete range of clean energy challenges, technologies, and associated issues. This book highlights synergistic opportunities, showing how energy efforts in different sectors can be integrated, capitalizing on the strengths of each to create better, more cost-effective solutions. This book enables professionals to discover what these opportunities mean at local, regional, and global scales, and learn how different stakeholder priorities can be effectively managed -- Source other than Library of Congress.
Keywords: Renewable energy sources.; elektronické knihy; electronic books